Morphological and electrical disturbances after split-flow fractionation in murine macrophages (2019)
Split-flow fractionation (SPLITT) is a family of techniques that separates in the absence of labeling using very low flow rates and force fields, and is therefore expected to minimize cell damage. Although it has been documented that separation methods cause physiological changes in immune cells that are attributable to mechanical stress and antibody labeling, SPLITT has not yet been examined for possible damaging effects of hydrodynamic stress, partly because it is assumed that the low flow rates and weak forces used in this technique do not generate significant mechanical stress. The aim of this study was to investigate the effects of SPLITT on cell function of a murine macrophage cell, and to compare these effects with those induced by centrifugation. Macrophages J774.2 were cultured in RPMI-enriched media, then detached from the culture flask and resuspended for 12 h. Cell suspensions were diluted in a buffered saline solution and exposed to SPLITT (flow rates 1–10 ml/min) or centrifugation (100–1500g) for 10 min. Cell viability, diameter, membrane potential, and nitric oxide production were measured. Under the operating conditions employed, cell viability was above 98% after SPLITT and centrifugation but cells suffered immediate hydrodynamic cell damage, including decreased cell diameter and membrane hyperpolarization which was inhibitable by 4-aminopyridine; nitric oxide production was not affected. Pressure values during SPLITT and centrifugation correlated with diameter and membrane potential. Our data do not support the assumption that SPLITT is innocuous to cell function. Some changes in SPLITT channel design are suggested to minimize cell damage. Membrane potential and cell diameter are sensitive indicators for the evaluation of sublethal damage in different cell models, and allow identification of optimal operating conditions on different scales. © 2019 Elsevier B.V.